Kiai Leadership Concept in The Scope of Pesantren Organizational Culture - Siti Aisyah; Munaya Ulil Ilmi; Muhammad Amirudin Rosyid; Eni Wulandari; Fandi Akhmad (Pascasarjana Pendidikan Agama Islam Institut KH. Abdul Chalim Mojokerto, 2022)
Leadership in the organizational culture of pesantren (Islamic Boarding School) has characteristics following the pesantren culture and prevailing religious values. As the pesantren leader, Kiai leads in a charismatic style that is full of authority and responsibility. This study aims to review the leadership of the Kiai in the organizational culture of the pesantren. It was assessed by using a library research model. The results showed that the administration of the Kiai had a significant influence on the achievement of the goals of the pesantren. Leadership values ​​are expected to be passed down from generation to generation to future leaders. The leadership of a Kiai and the culture of the Islamic boarding school are two things that influence each other. The Kiai's task as the pesantren leader is to form a personal commitment to the pesantren as an Islamic educational institution. A Kiai must maintain the culture or culture of the Islamic boarding school that has been preserved for centuries.